Paediatric Medicines: Regulatory and Scientific Issues - Daousani, Chrysa; Karalis, Vangelis D. (Drug Research, 2017)
In the past, dosage regimens authorized for adults were extrapolated to children relying mainly on empirical dosage adjustments. However, children are not small adults, but a distinct and heterogeneous group in terms of physiology, disease occurrence, pharmacokinetics, pharmacodynamics and also psychological, cognitive, and behavioral aspects. Even though it would be helpful to know the physiological changes and the special drug treatment needs in children, this task could not be performed due to ethical reasons. Important issues to consider for the development of paediatric drug products refer to the administration of the accurate dose, the use of the appropriate excipients, and acceptability. The latter is crucial and taste-screening methods (like electronic tongues) have been developed. A new era in paediatric medicines started with the entry into force of paediatric regulations. In the early ‘80s, the FDA started the set-up of a regulatory framework by authorizing issues like the Paediatric Rule, the Best Pharmaceuticals for Children Act, the Paediatric Research Equity Act, and the Food and Drug Administration Safety and Innovation Act. Similar efforts have been made in the EU, mainly through the entry into force of the Paediatric Regulation and the establishment of the Paediatric Committee, the Paediatric Investigation Plan, the Paediatric Use Marketing Authorization, and the European Paediatric Research Network. Other efforts to bridge the gap, between knowledge in adults and the children’s special requirements, include the extrapolation concept of safety/efficacy aspects, the application of modeling/simulation approaches in paediatric drug development, and the development of a paediatric Biopharmaceutics Classification Scheme.
Keywords: Paediatric medicines; Paediatric regulatory framework; Extrapolation concept